Opioid Analgesia for Medical Abortion: A Randomized Controlled Trial. Issue 6 (December 2019) - Colwill, Alyssa Covelli; Bayer, Lisa L.; Bednarek, Paula; Garg, Bharti; Jensen, Jeffery T.; Edelman, Alison B.
Abstract : OBJECTIVE: To estimate the effect of oral opioids on patient pain during first-trimester medical abortion. METHODS: We conducted a randomized, double-blind, placebo-controlled trial where patients up to 10 0/7 weeks of gestation undergoing a medical abortion with mifepristone and misoprostol took 10 mg oral oxycodone or placebo at onset of painful cramping. Additionally, all patients received 800-mg ibuprofen tablets, 4-mg ondansetron oral dissolving tablets, and a written prescription for adjunctive pain medication (six tablets oxycodone 5 mg). Participants used a text-messaging service to report pain scores on a numerical rating scale from 0 to 10 (0 being no pain, 10 being worst pain) for 24 hours at start of misoprostol dosing. The primary outcome was maximum pain experienced within 24 hours postmisoprostol. Our secondary outcomes were maximum pain stratified by gestational age (less than 7 weeks of gestation, 7–10 weeks of gestation), duration of maximum pain, use of adjunctive medication, presence of nausea or vomiting, and satisfaction. We needed at least 76 participants per group to differentiate a clinically important pain difference of 2 points on the numerical rating scale. RESULTS: From May 2017 to May 2018, we randomized 172 participants (placebo group with 86, oxycodone group with 86). The study groups had comparable baseline characteristics. We found no difference between groups in median maximum pain scores (placebo 8 [range 1–10], oxycodone 8 [range 2–10], P =.92) and the median duration of maximum pain (placebo 0.75 hours range 0.01–15 vs oxycodone 1 hour range 0.02–10, P =.39). Groups were also similar in the proportion obtaining (placebo 62%, oxycodone 49%, P =.09) and using (placebo 48%, oxycodone 40%, P =.28) adjunctive medication, experiencing nausea or vomiting (placebo 59%, oxycodone 65%, P =.43) and reported satisfaction with pain medications (placebo 62%, oxycodone 65%, P =.63). CONCLUSION: Oxycodone does not reduce the maximum level of pain experienced by women undergoing medical abortion up to 10 0/7 weeks of gestation or improve satisfaction. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, NCT03139240. Abstract : Oxycodone does not reduce the maximum level of pain experienced by women undergoing medical abortion up to 10 0/7 weeks of gestation.